Double blind, randomized controlled trial, to evaluate the effectiveness of a controlled nitric oxide releasing patch versus meglumine antimoniate in the treatment of cutaneous leishmaniasis [NCT00317629] - Silva Federico A; Mosquera Hernando; Muñoz Gerardo; Smith Daniel J; Rueda-Clausen Christian F; Vélez Iván D; López Marcos; Rueda Ligia C; Silva Sandra Y; Buitrago Adriana; Díaz Holger; López-Jaramillo Patricio (Trials, 2006)
Abstract Background Cutaneous Leishmaniasis is a worldwide disease, endemic in 88 countries, that has shown an increasing incidence over the last two decades. So far, pentavalent antimony compounds have been considered the treatment of choice, with a percentage of cure of about 85%. However, the high efficacy of these drugs is counteracted by their many disadvantages and adverse events. Previous studies have shown nitric oxide to be a potential alternative treatment when administered topically with no serious adverse events. However, due to the unstable nitric oxide release, the topical donors needed to be applied frequently, making the adherence to the treatment difficult. The electrospinning technique has allowed the production of a multilayer transdermal patch that produces a continuous and stable nitric oxide release. The main objective of this study is to evaluate this novel nitric oxide topical donor for the treatment of cutaneous leishmaniasis. Methods and design A double-blind, randomized, double-masked, placebo-controlled clinical trial, including 620 patients from endemic areas for Leishmaniasis in Colombia was designed to investigate whether this patch is as effective as meglumine antimoniate for the treatment of cutaneous leishmaniasis but with less adverse events. Subjects with ulcers characteristic of cutaneous leishmaniasis will be medically evaluated and laboratory tests and parasitological confirmation performed. After checking the inclusion/exclusion criteria, the patients will be randomly assigned to one of two groups. During 20 days Group 1 will receive simultaneously meglumine antimoniate and placebo of nitric oxide patches while Group 2 will receive placebo of meglumine antimoniate and active nitric oxide patches. During the treatment visits, the medications will be daily administered and the presence of adverse events assessed. During the follow-up, the research group will visit the patients at days 21, 45, 90 and 180. The healing process of the ulcer, the health of the participants, recidivisms and/or reinfection will also be assessed. The evolution of the ulcers will be photographically registered. In case that the effectiveness of the patches is demonstrated, a novel and safe therapeutic alternative for one of the most important public health problems in many countries will be available to patients.